Kepribadian Ekstrovert dan Introvert dalam Konteks Komunikasi Antarpribadi Mahasiswa Ilmu Komunikasi UNTIRTA - Subtinanda, Adhitya; Yuliana, Nina (Indonesian Journal Publisher, 2023)
The classification of personality into extroverted and introverted reflects communication patterns and social interactions of individuals. While communicating and socializing, individuals with extroverted personalities tend to be friendly, impulsive, and exhibit cheerful, active, fluent, and optimistic traits. They also display other characteristics that reflect high value on social relationships. On the contrary, individuals with introverted personalities have traits opposite to extroverts; they are more reserved, passive, less sociable, meticulous, pessimistic, calm, and controlled. This study aims to explore how the differences between extroverted and introverted personalities affect communication in student relationships. Students are an interesting group to study because they face various communication situations in daily life, including interactions with peers, professors, colleagues, and family. In this research, data collection techniques involve in-depth interviews. Interviews are conducted directly with Communication Science students at Untirta who have extroverted and introverted personalities. The researcher will gather authentic data supporting this study through direct interviews with respondents, as well as through relevant sources related to the research topic.